Morphometric Analysis of Adult Dermacentor parumapertus Neumann (Acari: Ixodidae) From Various Locations Within its Geographical Range. Issue 4 (27th February 2018) - Moraru, Gail M; Portugal, José Santos; Bednarova, Andrea; Mcinnis, Sarah J; Paddock, Christopher D; Becker, Tom; Smith, Travis C; Svobodova, Zdenka; Goddard, Jerome
Abstract: Dermacentor parumapertus Neumann (Acari: Ixodidae), a tick primarily associated with rabbits which occurs over much of the western United States, has a fairly large north-to-south distribution, being found from central Idaho southward into northern Mexico. This mostly obscure tick species has recently been the focus of attention due to the discovery of a unique strain of Rickettsia parkeri associated with it which appears closely related to a Rickettsia sp. found in the Atlantic rainforest of Brazil. Historically, a morphological variety of this species was reported in the literature based on significant variation in ornamentation of the tick throughout its range. This study examines several key morphological characters to determine if there are indeed more than one distinct population of this species throughout its range.